Sleep disorders in obese children are not limited to obstructive sleep apnoea syndrome. (22nd December 2017) - Carriere, Caroline; Coste, Olivier; Meiffred‐Drouet, Marie‐Claire; Barat, Pascal; Thibault, Hélène
Abstract: Aim: This study was to characterise respiratory and nonrespiratory sleep disorders in obese children and evaluate the diagnostic and therapeutic impact of a specific sleep consultation. Methods: A descriptive study was conducted in obese French children who received multidisciplinary care management from the hospital centre for paediatric obesity in Bordeaux. This followed a specific sleep consultation between 2007 and 2015, because their paediatrician had identified symptoms suggestive of sleep disorders. Results: The sleep specialist confirmed the presence of a sleep disorder in 98.4% of the 128 obese children, with a mean age of 12.1 ± 3.2 years. These included respiratory sleep disorders, hypersomnolence, insomnia and circadian rhythm sleep–wake disorders. Polysomnography revealed that 46.1% had respiratory sleep disorders and 24.2% had obstructive sleep apnoea syndrome (OSAS). Just under half (47.6%) were referred to an otorhinolaryngologist for sleep care management, 30.5% were referred to an orthodontist, 17.9% had melatonin treatment and 13.3% received continuous positive airway pressure ventilation. Conclusion: Sleep disorders in obese children were not limited to respiratory sleep disorders including OSAS. A systematic specific consultation with a sleep specialist is essential for the diagnosis and care of such children and would be beneficial when treating paediatric obesity.